Evaluating effectiveness of dust by-product treatment with scrubbers to mitigate explosion risk in ZrO2 atomic layer deposition process - Lee, Kwangho; Song, Dooguen; Lee, Jechan; Lee, Chang Gu; Shin, Gwy Am; Jung, Seungho (Journal of Hazardous Materials, 2020)
In processes of manufacturing semiconductors, reactive by-products (as a form of fine powder, i.e., dust) are deposited in pipes installed on post processing and exhaust systems, potentially involving a considerable explosion risk. In this study, the effectiveness of scrubber methods (e.g., dry scrubber and burn-wet scrubber) to mitigate the risk was evaluated. To this end, three by-products generated from a ZrO2 atomic layer deposition (ALD) process were collected from semiconductor manufacturers, which were treated with different methods (i.e., no treatment, treatment using dry scrubber, and treatment using burn-wet scrubber), and their characteristics were analyzed and compared. Particle size measurements of the by-products proved that the burn-wet scrubber treatment less decreased their particle size than the dry scrubber treatment. The burn-wet scrubber treatment made the by-product thermally stable, confirmed by thermogravimetric analysis. Fourier-transform infrared spectroscopy of the by-products before and after the scrubber treatments showed that burn-wet scrubbing of the by-product decreases surface functionalities that play a role in explosion. Dust explosion testing proved that robustness of explosion of the untreated by-product is about 7 times higher than the by-product treated with the burn-wet scrubber. Based on the results of this study, it would be suggested that burn-wet scrubber is a useful treatment method to decrease the explosion risks caused by dust by-products generated from ALD in semiconductor manufacturing processes.
Keywords: Particle size measurement; Post processing; Scrubber method; Semiconductor manufacturers; Semiconductor manufacturing process; Surface functionalities; Thermally stable; Treatment methods; Atomic layer deposition process; Dust by-product; Explosion hazard; Industrial waste; Semiconductor industry